Metagenomic analysis of microbial community in over-fermented tempeh - ARTINI PANGASTUTI; RIZAL KHOIRUN ALFISAH; NUR IFFAH ISTIANA; SITI LUSI ARUM SARI; RATNA SETYANINGSIH; ARI SUSILOWATI; TJAHJADI PURWOKO (Society for Indonesian Biodiversity, 2019)
Abstract. Pangastuti A, Alfisah RK, Istiana NI, Sari SLA, Setyaningsih R, Susilowati A, Purwoko T. 2019. Metagenomic analysis of microbial community in over-fermented tempeh. Biodiversitas 20: 1106-1114. Tempeh is a traditional Indonesian food which is made from soybeans through a fermentation process using Rhizopus as a starter culture. Tempeh is now considered as a functional food with many beneficial effects to human health beyond its nutritional value. The microbial community during the further fermentation process of tempeh give typical characteristic taste and flavor. Therefore the over-fermented tempeh is used as a flavoring in some dishes. Metagenomic analysis needed to know the involvement of microbial communities since most of the microbes involved in further fermentation process are unculturable. This research aimed to study the diversity of the microbial community in the over-fermented tempeh (72 hours) using the metagenomic analysis. Seventeen OTUs of fungi in over-fermented tempeh were detected. Among them, 9 OTUs had significant abundance: six species were identified as Tryblidiopsis sichuanensis, Candida sp.2_1., Kluyveromyces marxianus, Trichosporon asahii, Trichosporon gracile, and Trichosporon ovoides, one species was identified in the order level Mucorales, and two fungi species could not be determined. Species of the order Mucorales was the dominant species in over-fermented tempeh (72 hours) with a relative abundance of 62.46%, followed by Kluyveromyces marxianus with a relative abundance of 3698%. Meanwhile, 132 OTUs of the bacterial community was detected, the predominant 10 genera were Chryseobacterium, Lactococcus, Lactobacillus, Streptococcus, Acetobacter, Novosphingobium, Comamonas, Escherichia, Klebsiella, and Stenotrophomonas, in which Lactobacillus agilis, Lactococcus sp., and Klebsiella sp., were most abundant with relative abundance of 27%, 26.3%, and 13% respectively.